In vitro Production of Dendritic Cells as Cancer Immunotherapy: Highlights on Sample Source, Culture Period, Differentiation and Maturation Cytokines - Facicilia, Geofanny; Sartika, Cynthia Retna; Rostinawati, Tina (Molecular and Cellular Biomedical Sciences, 2023)
Dendritic cells (DC) are antigen-presenting cells between innate and adaptive immune cells and commonly used as immunotherapy. Despite this promising potential, protocols detailing the specifics of the DC production are varied, affecting the potency of dendritic as immunotherapy. There are various factors affecting the production and DC potency, such as sample source, culture period, differentiation and maturation cytokines. Due to the limited number and quality of DC in humans, the monocyte could be isolated and differentiated to mature DC. The purity and viability monocytes shall be maintained to produce a high yield of DC. Negative sorting maintains the potency of DC as a therapeutic agent. Monocytes from umbilical cord blood (UCB) are naïve and can be differentiated to DC easily. Meanwhile, the tumor microenvironment (TME) may inhibit DC maturation from monocyte-derived peripheral blood. Without pro-inflammatory cytokines and a short maturation period, DC remain immature and fails to activate T cells. Long-period culture correlates with decreased DC viability and function. This review outlines several factors which can produce higher cytotoxic T cells and pro-inflammatory cytokines that might help each facility in developing its protocol to ensure the best procedure in DC production. Increasing purity and yield through close and automatic system under GMP production are mandatory to decrease risk of contamination during DC production.Keywords: differentiation cytokines, maturation cytokines, culture period, sample source, isolation technique